2018
DOI: 10.1017/s0025315418000887
|View full text |Cite
|
Sign up to set email alerts
|

Invertebrate recruitment on artificial substrates in the Red Sea: role of substrate type and orientation

Abstract: Surface physical properties, hydrodynamics, biochemical cues, orientation and temporal scales play an important role in invertebrate larval recruitment on artificial substrates. In the present study, invertebrate recruitment on four different substrates (acrylic, stainless steel, ceramic and concrete panels) was investigated in two different orientations (vertical and horizontal) in the central Red Sea. Results showed significant variations in the abundance of benthic invertebrates between the different substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…depending on whether coral heads are alive or dead (Gibson et al, 2011), with degraded reef frameworks exhibiting greater diversity (Enochs & Manzello, 2012;Nelson et al, 2016). Larval settlement of sessile reef invertebrates can be greater on artificial substrates (Higgins et al, 2019), in which community composition is affected by the orientation and composition of plates (Siddik et al, 2019), presence of microtopographies (Whalan et al, 2015), and grazing pressure (Hixon & Brostoff, 1985). The organisms that settle on plastic settlement plates such as those that comprise an ARMS structure may not be representative of the dominant organisms inhabiting coral carbonate structures (Zimmerman & Martin, 2004), although similarities have been found in prior surveys using ARMS (Pennesi & Danovaro, 2017;Plaisance et al, 2011).…”
Section: All Motus All Motus Idenɵfied To Ordermentioning
confidence: 99%
“…depending on whether coral heads are alive or dead (Gibson et al, 2011), with degraded reef frameworks exhibiting greater diversity (Enochs & Manzello, 2012;Nelson et al, 2016). Larval settlement of sessile reef invertebrates can be greater on artificial substrates (Higgins et al, 2019), in which community composition is affected by the orientation and composition of plates (Siddik et al, 2019), presence of microtopographies (Whalan et al, 2015), and grazing pressure (Hixon & Brostoff, 1985). The organisms that settle on plastic settlement plates such as those that comprise an ARMS structure may not be representative of the dominant organisms inhabiting coral carbonate structures (Zimmerman & Martin, 2004), although similarities have been found in prior surveys using ARMS (Pennesi & Danovaro, 2017;Plaisance et al, 2011).…”
Section: All Motus All Motus Idenɵfied To Ordermentioning
confidence: 99%
“…Substrate selection by larvae has been assessed by both field and laboratory experiments. In field experiments, test substrata are immersed in the field and the amounts of settlers are compared among the substrata under different conditions [1,2]. Results include both pre-settlement selection and post-settlement selection.…”
Section: Introductionmentioning
confidence: 99%
“…To develop such physical approaches against biofouling, it is necessary to elucidate the larval preference(s) of the physical properties of substrates for settlement. This review focuses on wettability and nano-structures of substrate surfaces for the substrate selection of ascidian larvae, while other factors of microhabitat influencing the pre-settlement selection were examined, such as the orientation of the substrate (i.e., vertical or horizontal) [2], nutrient contaminants in water [16], and textures of the substrate [9].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a growing number of field studies have demonstrated that larval settlement rates of calcifying marine invertebrates vary on common structural materials (e.g., concrete, stainless steel). 46,47 Further work has assessed the ability of different materials to promote the growth of settlement-inducing algae and microbial communities. 48,49 However, to our knowledge, larval settlement cues related solely to inorganic material composition have not yet been investigated systematically.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Thus, it is plausible that corals have evolved to seek out specific inorganic chemicals or materials during the larval stage that would indicate whether a location will be favorable for mineralization and skeletal attachment and support. Indeed, a growing number of field studies have demonstrated that larval settlement rates of calcifying marine invertebrates vary on common structural materials (e.g., concrete, stainless steel). , Further work has assessed the ability of different materials to promote the growth of settlement-inducing algae and microbial communities. , However, to our knowledge, larval settlement cues related solely to inorganic material composition have not yet been investigated systematically.…”
Section: Introductionmentioning
confidence: 99%